Holocene–late Pleistocene non-tropical carbonate sediments and tectonic history of the western rift basin margin of the southern Gulf of California - Halfar, J.; Godinez-Orta, L.; Goodfriend, G. A.; Mucciarone, D. A.; Ingle, J. C.; Holden, P. (Sedimentary Geology, 2001)
Using high-resolution seismic reflection profiling and dating of (1) shallow marine vibracores and (2) sediments collected from uplifted marine terraces we reconstruct the tectonic history and sediment accumulation patterns of Holocene to late Pleistocene warm-temperate to subtropical carbonates in the southern Gulf of California, Mexico. The study was conducted in the vicinity of La Paz where carbonates form along the fault bounded narrow western shelf of the tectonically active Gulf of California rift basin. The non-tropical nature of the setting is responsible for (1) poor cementation of the bioclastic carbonates, and (2) a composition which is dominated by rhodoliths (coralline red algae), corals and mollusks. Unrimmed carbonate flats forming in small pocket bays and a rhodolith bioherm, which has a surface area of more than 20 km2 and is up to 16 m thick, constitute the major carbonate factories. Holocene carbonate accumulation rates were deduced from seismic and core data and are highest on the rhodolith bioherm (260 cm/ka) and in subtidal zones of pocket bays (210 cm/ka), and lowest on the inner and middle shelf (100 cm/ka). Taken together, rates of carbonate accumulation are intermediate in magnitude between higher rates recorded in fully tropical carbonate settings and lower rates typical of cool-water carbonates. Seismic reflection profiles demonstrate that Isla Espiritu Santo in the center of the study area is a west dipping fault block, which is tectonically influenced by two distinct faults, the La Paz and Espiritu Santo faults. The latter fault accommodates at least 700 m of east-side down normal offset, and forms a steep eastern escarpment leading into the La Paz slope basin. Some of the sediments produced in the shallow carbonate factories of the narrow La Paz shelf are transported across this escarpment and are redeposited in the slope basin at a water depth of 750 m. Uranium-series dates of marine terraces exposed on Isla Espiritu Santo indicate that late Pleistocene uplift along the eastern side of the island could be as high as 310 mm/ka whereas downdropping along the western side of the island occurred at a rate of up to 15 mm/ka. Isla Espiritu Santo therefore constitutes part of the uplifted shoulder of the western margin of the Gulf of California rift basin. Patterns of vertical tectonic movements of Isla Espiritu Santo together with fault offsets on the surrounding seafloor and slump features on steep submarine slopes, point to continuous activity of the La Paz and Espiritu Santo faults. Results of this study will assist in recognizing and interpreting similar settings along ancient non-tropical rift basin margins worldwide and especially in the Neogene of the Gulf of California.
id: 1316